Clinical Impact of Heparin Kinetics During Catheter Ablation of Atrial Fibrillation: Meta‐Analysis and Meta‐Regression. (3rd May 2016) - BRICENO, DAVID F.; VILLABLANCA, PEDRO A.; LUPERCIO, FLORENTINO; KARGOLI, FARAJ; JAGANNATH, ANAND; LONDONO, ALEJANDRA; PATEL, JIGNESH; OTUSANYA, OLUFISAYO; BREVIK, JEANNINE; MARABOTO, CAROLA; BERARDI, CECILIA; KRUMERMAN, ANDREW; et al.
Anticoagulation for Ablation of Atrial Fibrillation: Introduction: Appropriate activated clotting time (ACT) during catheter ablation of atrial fibrillation (CA‐AF) is essential to minimize periprocedural complications. Methods and Results: An electronic search was performed using major databases. Outcomes were thromboembolic (TE) and bleeding complications according to ACT levels (seconds). Heparin dose (U/kg) and time (minutes) to achieve the target ACT was compared among patients receiving vitamin K antagonist (VKA) versus non‐VKA oral anticoagulants (NOAC). Nineteen studies involving 7, 150 patients were identified. Patients with ACT > 300 had less TE (OR, 0.51; 95% CI 0.35–0.74) and bleeding (OR, 0.70; 95% CI 0.60–0.83) compared to ACT < 300, when using any type of oral anticoagulation. The use of VKA was associated with reduced heparin requirements (mean dose: 157 U/kg vs. 209 U/kg, P < 0.03; SDM –0.86 [95% CI –1.39 to –0.33]), and with lower time to achieve the target ACT (mean time: 24 minutes vs. 49 minutes, P < 0.03; SDM –11.02 [95% CI –13.29 to –8.75]) compared to NOACs. No significant publication bias was found. Conclusions: Performing CA‐AF with a target ACT > 300 decreases the risk of TE without increasing the risk of bleeding. Patients receiving VKAs required less heparin and reached the target ACT faster compared to NOACs.